(untitled) (Third Sector Social Economic Review, 2024)
For many years, the relationship between financial development and economic growth has been questioned. In this context, the interest of academics as well as the high level of curiosity of practitioners draws attention. The fact that the subject has been discussed for many years has led to the emergence of many studies in the field. The number of studies in this field has increased in recent years. In this study, the relationship between the financial development index, national income, consumer confidence index, US Dollar Exchange Rate, and profitability ratios of banks has been tried to be examined. In the study, data obtained between 1990 and 2020 were used. According to the results obtained from the study, a causal relationship could not be determined between the financial development index and the national income, consumer confidence index, and the US Dollar exchange rate. On the other hand, a causal relationship was found between the financial development index and the profitability ratios of banks. In other words, there is a relationship between the financial development index and bank profitability ratios, and as the financial development index rises, the profitability of the banks also increases. On the other hand, in both models, there is no causal relationship between the financial development index and consumer confidence, per capita GNP, and the US Dollar exchange rate. The results obtained from the study were also compared with previous studies. According to the findings, the study shows parallelism with the findings obtained in the following studies: De Gregorio and Guidotti (1995), Singh (1997), Rousseau and Wachtel (2000), Arestis et al. (2001), Calderon and Liu (2003), Rioja and Valev (2004), Atindehou et al (2005), Afsar (2008), Narayan and Narayan (2013), Menyah et al (2014), Grassa and Gazdar (2014), Ductor and Grechyna (2015), Inancli et al (2016) , Opoku et al. (2019). At the same time, a positive relationship was found between financial development and bank profitability. Studies showing parallelism in this context are: Ting (2017), Sufian and Habibullah (2009), and Flamini et al. (2009).